Kadrovski management od industrijske revolucije do digitalizacije - Ferjan, Marko (2018)
Human Resource Management from Industrial Revolution to Digitization. Whatever the definition we use to answer to the question “what is HRM?”, the answer consist of people in organizations. The term Human Resource Management has been faced with major evolution after industrial revolution in Europe. It is used to describe formal systems devised for the management of people within an organization. Human Resource Management is responsible for effective designing and implementation of various policies, procedures and programs. It is all about developing and managing knowledge, skills, creativity, aptitude and talent and using them optimally. Human Resource Management has four basic functions: staffing, training and development, motivation and maintenance. The Human Resource Management function is a critical component of any organization. The basic mission of Human Resource Management will always be to acquire, develop, and retain talent; align the workforce with the business; and be an excellent contributor to the business.
Keywords: Human Resource Management; workforce; staffing; training; development